Temporal changes in the genotypes of methicillin-resistant Staphylococcus aureus strains isolated from a tertiary Malaysian hospital based on MLST, spa, and mec-associated dru typing - Lim, King Ting; Hanifah, Yasmin Abu; Yusof, Mohd Yasim Mohd; Goering, Richard V.; Thong, Kwai Lin (Elsevier, 2012)
Methicillin-resistant Staphylococcus aureus (MRSA) is one of the main bacterial pathogens responsible for nosocomial infections leading to pneumonia, bloodstream, skin, and soft tissue infections. The objective of this study was to investigate the genomic changes of MRSA in a tertiary hospital between the years 2003, 2004, 2007, and 2008. One hundred fifty-four MRSA strains were characterized by multilocus sequence typing (MLST), spa, and mec-associated dru typing. Among the 154 strains, 29 different dru, 15 spa, and 8 MLST types were identified. Seven sequence types (STs) (ST239, ST22, ST5, ST6, ST80, ST573, and ST241) were identified among 2007–08 strains, although only 2 STs (ST239 and ST20) were observed among 2003 strains. Clones ST239-t037-dt13g, ST22-t032-(dt10a and dt10aw), and 28 other MRSA clones being introduced in 2007–2008 have replaced the ST239-t037 (dt13d, 14h, 13i, 13l, 13m, 15m, 15l, and 11al) clones present in 2003. The predominant MLST clone, ST239 (90.3%), was further distinguished into 7 different spa types and 26 different dru types, including 17 novel dru types. Maximum parsimony tree based on dru repeats revealed that 10 dru types (dt11am, dt13j, dt15n, dt13q, dt13n, dt13p, dt13f, dt13ao, dt12j, dt7v) shared the same MLST–spa types with dt13d, suggesting that these MRSA clones might have evolved from ST239-t037-dt13d. In conclusion, our data showed that the ST239-t037-dt13d clone and other MRSA clones in 2003 were replaced by ST239-t037-dt13g and other new emerging spa and dru types.